PKM GURU SMA YPPI 2 MELALUI TRANSFORMASI TEKNOLOGI PEMBELAJARAN JARAK JAUH - darmanto, darmanto; Prayitno, Agus; Hermawan, Budi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2021)
ABSTRACT The Covid-19 pandemic is still happening. The problems encountered during Distance Learning (DL), are the teacher’s difficulties in adapting to it and the lack of students' motivation. The limited equipment of IT is also experienced by YPPI2 Senior High School. In addition, the government encourages the implementation of Face-to-face Learning (FFL), so the school management can remain optimal. However, our partner, YPPI2 does not have yet a Learning Management System (LMS) as a medium to support the Teaching and Learning Process. To overcome it, Uwika Community Partnership Program (CPP) offers a solution by using LMS as a medium for DL. This program uses training and mentoring methods. Technological transformation is applied to users who act as administrators, teachers, and students through LMS based on Moodle application. This application is specially designed to make it easier for teachers and students to communicate during DL. The purpose is to help the users to adapt to LMS technology and Moodle applications. The results indicate that there is an increase in participants' ability regarding LMS and Moodle application. The participants are significantly good enough in implementing e-learning practices. Keywords: Distance Learning, Learning Management System, Moodle